Helicobacter pylori infection in gastric carcinoma in the Van region of Turkey - , M. Kürşat TÜRKDOĞAN, Süleyman ALICI, Mahmut İLHAN, Hüsniye DİLEK, Emel AKMAN, Hayati AYAKTA, Metin KARAKÖK (Turkish Journal of Gastroenterology 1, 2019)
-